2008
DOI: 10.1111/j.1745-7254.2008.00745.x
|View full text |Cite
|
Sign up to set email alerts
|

5-HT1A/7receptor agonist excites cardiac vagal neurons via inhibition of both GABAergic and glycinergic inputs

Abstract: Aim: To study the synaptic mechanisms involved in the 5-hydroxytryptamine1A/7 (5-HT 1A/7 ) receptor-mediated reflex control of cardiac vagal preganglionic neurons (CVPN). Methods: CVPN were retrogradely labeled and identified in brain stem slices of newborn rats, and their synaptic activity was examined using whole-cell patch-clamp. Results: 8-Hydroxy-2-(di-N-propylamino) tetralin (8-OH-DPAT), an agonist of 5-HT 1A/7 receptors, had no effect on the glutamatergic inputs of CVPN. In contrast, it significantly de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 34 publications
1
6
0
Order By: Relevance
“…However, a recent study in rats reported that strychnine sensitive glycine receptors are not involved in tonic or reflex control of cardiac vagal output (Hildreth and Goodchild, 2010) but are needed for 5H 1A receptor activation induced facilitation of bradycardia and changes in heart rate (Hildreth and Goodchild, 2010). In support of the current findings differential sensitivity of GABA and glycinergic neurons and inputs projecting to CVNs has been reported previously in which spontaneous glycinergic IPSCs were more sensitive to neuromodulators such as orexin-A (Wang et al, 2005) and 5HT 1A/7 receptor agonists (Chen et al, 2008) compared to GABA IPSCs. These reports indicate that GABA and glycine inputs to CVNs are likely differentially regulated, including their modulation by dopamine.…”
Section: 0 Discussionsupporting
confidence: 92%
“…However, a recent study in rats reported that strychnine sensitive glycine receptors are not involved in tonic or reflex control of cardiac vagal output (Hildreth and Goodchild, 2010) but are needed for 5H 1A receptor activation induced facilitation of bradycardia and changes in heart rate (Hildreth and Goodchild, 2010). In support of the current findings differential sensitivity of GABA and glycinergic neurons and inputs projecting to CVNs has been reported previously in which spontaneous glycinergic IPSCs were more sensitive to neuromodulators such as orexin-A (Wang et al, 2005) and 5HT 1A/7 receptor agonists (Chen et al, 2008) compared to GABA IPSCs. These reports indicate that GABA and glycine inputs to CVNs are likely differentially regulated, including their modulation by dopamine.…”
Section: 0 Discussionsupporting
confidence: 92%
“…In support of this hypothesis, in slice preparation, application of 8-OH-DPAT inhibits both GABAergic and glycinergic inputs to CVPN [26,27]. To confirm the physiological relevance of these findings we blocked GABA A receptors or strychnine-sensitive glycine receptor in the vicinity of CVPN and examined the response of systemic 8-OH-DPAT on the tonic and reflex bradycardia evoked.…”
Section: Discussionmentioning
confidence: 98%
“…Speculation suggests that as the 5-HT 1A receptor is an inhibitory GPCR, the mechanism must involve an interaction with inhibitory ionotropic inputs to CVPN [25]. In keeping with this hypothesis, application of 8-OH-DPAT in vitro attenuates presynaptic GABAergic and glycinergic inputs to CVPN [26,27]; however the functional significance of these inputs is unknown. Whether or not the effects of 5-HT 1A activation on HR or BRS are mediated by GABAergic and/or glycinergic inhibition of CVPN in the ventrolateral medulla has not been investigated in vivo .…”
Section: Introductionmentioning
confidence: 99%
“…Activation of 5-HT 1A and 5-HT 1B receptors leads to the hyperpolarization of the neurons and reduction of the GABA release in different parts of CNS e.g. cerebellum or dorsal raphe nucleus (Chen et al, 2008;Ostrowski et al, 2014).…”
Section: Page 17 Of 26mentioning
confidence: 99%